2021
DOI: 10.5380/riep.v25i2.60759
|View full text |Cite
|
Sign up to set email alerts
|

Adaptação parental ao filho com deficiência: revisão sistemática da literatura

Abstract: Quando nasce uma criança com deficiência, é necessária a reidealização do filho para que os pais possam lidar com as suas limitações e atender as suas demandas, resultando em uma adaptação parental adequada ao filho real. O presente artigo objetivou realizar uma revisão sistemática sobre a adaptação parental. Para tanto, investigaram-se as bases de dados Pubmed, BVS, Scopus e Cochrane, utilizando os termos Family adaptation, family impact, disabled children, no período de agosto a setembro de 2017. Foram anali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
11

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 18 publications
0
3
0
11
Order By: Relevance
“…Until a diagnosis is confirmed, many mothers go through several health professionals and institutions (Lopes et al, 2019). The way in which the diagnosis is presented is of great importance, as it conveys information about what it is, what the prognosis is and demands for care and treatment, which favors that mothers feel enlightened, guided and welcomed (Londero et al, 2021). The greater the knowledge about the condition of the child, the more qualified the mothers are to deal with their development and with their own emotions, being able to review beliefs and values about the child (Glat & Pletsch, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Until a diagnosis is confirmed, many mothers go through several health professionals and institutions (Lopes et al, 2019). The way in which the diagnosis is presented is of great importance, as it conveys information about what it is, what the prognosis is and demands for care and treatment, which favors that mothers feel enlightened, guided and welcomed (Londero et al, 2021). The greater the knowledge about the condition of the child, the more qualified the mothers are to deal with their development and with their own emotions, being able to review beliefs and values about the child (Glat & Pletsch, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In a literature review, Londero et al (2021) found that for the process of parental adaptation to occur, there must be an early identification of the negative and positive factors that influence the child's re-idealization process, the existence of a family-centered approach focused on solving family problems and, ultimately, building support networks aimed specifically at families with children with disabilities and/or neurodevelopmental disorders.…”
Section: Discussionmentioning
confidence: 99%
“…O nascimento de uma Pessoa com Deficiência (PCD) é caracterizado por inúmeras mudanças no âmbito familiar, sobretudo, com relação aos pais. De acordo com Sales (2016) quando os pais recebem informações acerca do diagnóstico, o qual afirma que o bebê será uma PCD, é comum que os mesmos manifestem reações de negação, seguidas de raiva, barganha ou negociação, culpa e aceitação, sendo este período caracterizado como um processo de luto (LONDERO et al, 2021).…”
Section: Introductionunclassified
“…A literatura destaca o impacto que o nascimento de uma criança com deficiência representa numa família, mas também reconhece que esta situação poderá ser definitiva e acompanhar a família ao longo dos tempos, sendo crucial estudar continuamente estas famílias, não se limitando à infância, dado que se assiste a um aumento da esperança média de vida (Oliveira & Poleto, 2015). A entrada do filho com deficiência na fase adulta e as transições com as quais a família se depara ao longo do ciclo vital, a par com a deficiência, representam enormes desafios e apresentam especificidades, que podem fragilizar a esfera familiar (Londero et al, 2021;Pereira, 2018).…”
unclassified
“…Neste sentido, a deficiência congénita ou adquirida gera uma crise no sistema familiar, afetando toda a dinâmica familiar e função familiar, bem como as perspetivas para o futuro, exigindo reconstrução dos papéis, na estrutura e estilo de vida familiar (Londero et al, 2021) (Cedeño et al, 2020).…”
unclassified